Utilization of the ART approach in a group of public oral health operators in South Africa: a 5-year longitudinal study - Frencken Jo E; Mickenautsch Steffen (BMC, 2009)
Abstract Background A significant increase in the proportion of restorations to the number of tooth extractions was reported after the introduction of ART in an academic mobile dental service in South Africa. The changes were ascribed to its less threatening procedure. Based on these findings, ART was subsequently introduced into the public oral health service of Ekurhuleni district in the South African province of Gauteng. This article reports on the 5-year restorative treatment pattern of operators in the Ekurhuleni district, who adopted the ART approach into their daily dental practice. Methods Of the 21 trained operators, 11 had placed more than 10% of restorations using ART at year 1 and were evaluated after 5 years. Data, including number of restored and extracted teeth and type of restoration, were drawn from clinical records 4 months before, and up to 5 years after training. The restoration/extraction ratio (REX score) and the proportion of ART restorations to the total number of restorations were calculated. The paired sample t-test and linear regression analysis were applied. Results The mean percentage of ART restorations after 1 year was 24.0% (SE 7.2) and significantly increased annually to 42.7% (SE 9.2) after 5 years in permanent dentitions. In primary dentitions the mean percentage of ART restorations after 1 year was 80.6% (SE 4.9) and 72.6% (SE 8.8) after 5 years. The mean REX score before ART training was 0.08 (SE 0.03) and 0.07 (SE 0.04) for permanent and primary teeth, respectively and 0.11 (SE 0.03) and 0.17 (SE 0.05) after 5 years. Conclusion Five years after training, ART had been used consistently in this selected group of operators as the predominant restorative treatment used for primary teeth and showed a significant annual increase in permanent teeth. However, this change had not resulted in an increase in the REX score in both dentitions.